PENEGAKAN HUKUM TERHADAP PELAKU PENGANCAMAN PORNOGRAFI (Study Kasus Polres Lampung Utara) - Ibrahim Fikma Edrisy; Fahrul Rozi (Legalita, 2021)
This study intends to identify law enforcement against perpetrators of pornography condemnation based on Article 45 paragraph (1) and Article 27 paragraph (1) of the ITE Law, as well as determine what variables prevent pornography condemnation. ITE This is a study of legal principles. The case under investigation will be thoroughly investigated by researchers. Secondary data is the type of information used. Primary legal documents, secondary legal materials, and tertiary legal materials were used as secondary data sources. Primary and secondary data are the types of data collected by the writers in this study. Data that is directly obtained from a source is referred to as primary data